Letter - Winstanley, E.
032-0202-001 TELEGRAPHIC ADDRESS: INLAND-"WHOLESALE, MANCHESTER." FOREIGN-"COPEXPORT, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. EXTENSION NO. 87 PLEASE ADDRESS YOUR REPLY: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. CABLE CODES: A.B.C. 6TH AND 7TH EDITIONS; WESTERN UNION 8 LETTER; BENTLEY COMPLETE PHRASE; BENTLEY SECOND PHRASE; A.1. MARCONI, AND PRIVATE. Our Reference: EXPORT 1733 ST/HP. Your Reference: 4th November, 1938. The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, We confirm the message transmitted to you today through the medium of our London Branch, relative to the invoice for Sandals enclosed with our letter of yesterday's date. When originally quoting, we intimated that the goods were supplied f.o.b. English port, packing included, but inadvertently our Invoice Department have made a charge for cases. We are enclosing herewith amended invoice, and shall be glad if you will return the other at your convenience. Yours faithfully, E. Winstanley Export Department. E.A.B. Invoice amount £313.9.4. 292/946/32/202